Response of Sodium Bicarbonate Sodicity on Survival, Seedling Growth and Plant Nutrients of Four Multipurpose Arid Trees - Toky, O P; Srinivasu, V (Annals of Arid Zone, 2025)
Acacia nilotica (L.) Willd. ex Del., Albizia lebbek, Pitecellobium dulce and Prosopis cineraria, were grown in sodic soils of 20 to 100 ESP. Seedings did not survive above 45 ESP in P. dulce, 60 ESP in A. nilotica and A. lebbek, and 80 ESP in P. juliflora. Seedlings did not survive above 45 ESP in P. juliflora. In 5-month-old plants, plant height. biomass production and leaf area decreased, while the leaf thickness increased with rising level of sodicity. Plant nutrient concentration varied significantly (P < 0.05) among the species and sodicity levels. N, P, K, Ca and Mg decreased and Na concentration increased with increase in ESP. Maximum reduction in Ca and P concentration was observed in the leaves of P. jrrliflora and A. ttilotica, and in roots and stems of the remaining two species. The higlier content of Na in roots and lower content in leaves may be adaptive strategies of A. juliflora and P. juliflora to survive under high levels of sodicity. The results are useful for afforestation and management of sodic soils.